A general frequency adaptive framework for damped response analysis of wind turbines. Issue 143 (April 2021) - Adhikari, S.; Bhattacharya, S.
Abstract: Dynamic response analysis of wind turbine towers plays a pivotal role in their analysis, design, stability, performance and safety. Despite extensive research, the quantification of general dynamic response remains challenging due to an inherent lack of the ability to model and incorporate damping from a physical standpoint. This paper develops a frequency adaptive framework for the analysis of the dynamic response of wind turbines under general harmonic forcing with a damped and flexible foundation. The proposed method is founded on an augmented dynamic stiffness formulation based on a Euler-Bernoulli beam-column with elastic end supports along with tip mass and rotary inertia arising from the nacelle of the wind turbine. The dynamic stiffness coefficients are derived from the complex-valued transcendental displacement function which is the exact solution of the governing partial differential equation with appropriate boundary conditions. The closed-form analytical expressions of the dynamic response derived in the paper are exact and valid for higher frequency ranges. The proposed approach avoids the classical modal analysis and consequently the ad-hoc use of the modal damping factors are not necessary. It is shown that the damping in the wind turbine dynamic analysis is completely captured by seven different physically-realistic damping factors. Numerical results shown in the paper quantify the distinctive nature of the impact of the different damping factors. The exact closed-form analytical expressions derived in the paper can be used for benchmarking related experimental and finite element studies and at the initial design/analysis stage. Highlights: Use of Dynamic Stiffness method. Exact closed for expression for dynamic damped response of Offshore Wind Turbines. Damping modelled using 7 physically realistic damping factors. Example application of the model shown.